2016
DOI: 10.3389/fmars.2016.00099
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Speciation of Dissolved Iron in Jiaozhou Bay (Yellow Sea, China)

Abstract: The distribution of total dissolved iron (DFe) and its chemical speciation were studied in vertical profiles of the shallow and semi-closed Jiaozhou Bay (JZB, China) during two contrasting periods: summer (July 19 th , 2011) and spring (May 10 th , 2012). Samples collected from the surface, middle and bottom layers were analyzed by competitive ligand exchange-adsorptive cathodic stripping voltammetry (CLE-aCSV). The mean DFe concentration during the summer period (median 18.8 nM; average 20.7 nM) was higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
(81 reference statements)
2
5
0
Order By: Relevance
“…As DrFe was rarely studied in other areas, there was no comparison of DrFe. The TdFe results were comparable with those of East China Sea, Jiaozhou Bay, and Southern Yellow Sea (Table 3) [8,22,42], while iron contents from Sanggou Bay and two foreign coastal areas were much lower in comparison (Table 3). Table 3 shows that TdFe levels in seawater from sampling stations in the East China Sea were higher in spring than in autumn.…”
Section: Comparison Of Tdfe In Sishili Bay With Other Coastal Areassupporting
confidence: 66%
See 1 more Smart Citation
“…As DrFe was rarely studied in other areas, there was no comparison of DrFe. The TdFe results were comparable with those of East China Sea, Jiaozhou Bay, and Southern Yellow Sea (Table 3) [8,22,42], while iron contents from Sanggou Bay and two foreign coastal areas were much lower in comparison (Table 3). Table 3 shows that TdFe levels in seawater from sampling stations in the East China Sea were higher in spring than in autumn.…”
Section: Comparison Of Tdfe In Sishili Bay With Other Coastal Areassupporting
confidence: 66%
“…Iron fertilizing experiments in the high nutrient and low chlorophyll (HNLC) areas have indicated that adding iron can increase the growth of marine phytoplankton and influence local CO 2 absorption and nutrient consumption [6]. This further confirmed Martin's hypothesis from the 1990s [7] that the phenomenon of a high nutrient concentration but low biomass of phytoplankton in seawater was due to the low concentration of bioavailable iron [8]. However, iron limitations on phytoplankton growth may occur even though the total dissolved iron (TdFe) value is abundant; an example of this can be seen in Lake Kasumigaura of Japan, where iron concentrations were higher than those in oceanic waters while inorganic iron levels did not differ significantly [9].…”
Section: Introductionsupporting
confidence: 56%
“…To obtain more valuable experimental data, the total dissolved Fe concentration was determined and the relationship between Fe and TMs was further analyzed. The results showed that Fe concentrations were higher in Sishili Bay than in other areas (Nimmo et al, 1989;Su et al, 2016Su et al, , 2015Su et al, , 2017. The spatial distribution of the total dissolved Fe (annual average values) in the surface seawater of Sishili Bay is presented in Figure 8A.…”
Section: Relationship Of Tms With Micronutrient Metal (Fe)mentioning
confidence: 95%
“…As a mariculture area, it is very important to investigate the pollution level of seawater, especially the metal levels. Although various studies investigated TMs in seawater (Nimmo et al, 1989;Meng et al, 2008;Mao et al, 2009;Tian et al, 2009;Wang et al, 2012;Su et al, 2015Su et al, , 2016Su et al, , 2017Han et al, 2018), little information is available on the spatialtemporal distributions and species of TMs. However, studying the spatial-temporal distributions and species of TM is helpful to achieve a better understanding of the TM pollution degree in seawater and provides effective data support for aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…; Su et al . ). In the boxplot representations, the box shows the second and the third quartile (from left to right), separated by a vertical line, which represents the median.…”
Section: Introductionmentioning
confidence: 97%